PELATIHAN PEMBUKUAN SEDERHANA BAGI WANITA BERWIRAUSAHA DI KELURAHAN MELAYU KOTA PIRING TANJUNG PINANG - Satriadi Satriadi; Sri Kurnia; Dandy Lucky Pratama; Dian Ocviasari; Tassya Adita Megarani; Siti Nuraisyah Fitriani (Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the most important business sectors for Indonesia's economic development is Micro, Small and Medium Enterprises (MSMEs). The purpose of community service activities to train simple bookkeeping for entrepreneurial women in the Malay Village of Kota Piring is to be able to make simple bookkeeping so that they are orderly in carrying out financial records, so that expenses, income and profits can be seen. The method used is by way of training. The result obtained from this activity is to increase the ability and competence regarding new insights in running their business through simple bookkeeping that is easy to apply.